Temperature–Light Dual‐Responsive Au@PNIPAm Core‐Shell Microgel‐Based Optical Devices. (8th November 2018) - Wei, Menglian; Serpe, Michael J.
Abstract: Au nanoparticle (AuNP) core particles coated with a poly( N ‐isopropylacrylamide) (pNIPAm) shell (Au@pNIPAm) are synthesized by seed mediated free radical polymerization. Subsequently, a temperature–light‐responsive photonic device is fabricated by sandwiching the Au@pNIPAm particles between two thin layers of Au. The optical device exhibits visual color and characteristic multipeak reflectance spectra, where peak position is primarily determined by the distance between two Au layers. Dual responsivities of the photonic device are achieved by combining the photothermal effect of AuNPs core (localized surface plasmon resonance (LSPR) effect) and the temperature responsivity of the pNIPAm shell. That is, the pNIPAm shell collapses as the temperature is increased above pNIPAm's lower critical solution temperature, either by direct heat input or heat generated by AuNPs' LSPR effect. To investigate the effect of AuNPs distribution in the microgels on the devices' photothermal responsivity, the Au@pNIPAm microgel‐based etalon devices are compared with that fabricated by AuNP‐doped pNIPAm‐based microgels; in terms of response kinetics and optical spectrum homogeneity. The uniform Au@pNIPAm microgel‐based devices show a fast response and exhibit a comparatively homogeneous spectrum over the whole slide. These materials can potentially find use in drug delivery systems, active optics, and soft robotics. Abstract : Au@pNIPAm core‐shell microgel‐based optical devices change color as the temperature increases or upon exposing them to green light. The dual responsivity is a result of the thermoresponsivity of pNIPAm shell and photothermal properties of AuNP core. Such devices exhibit a faster response and more homogeneous reflectance spectra than devices made from AuNPs‐doped pNIPAm‐based devices.